Impact of combination therapy 5-alpha reductase inhibitors (5-ARI) plus alpha-blockers (AB) on erectile dysfunction and decrease of libido in patients with LUTS/BPH: a systematic review with meta-analysis. (2nd July 2016) - Favilla, Vincenzo; Russo, Giorgio Ivan; Privitera, Salvatore; Castelli, Tommaso; Giardina, Raimondo; Calogero, Aldo E; Condorelli, Rosita A; La Vignera, Sandro; Cimino, Sebastiano; Morgia, Giuseppe
Abstract: Lower urinary tract symptoms (LUTS) secondary to benign prostatic obstruction (BPO) represent one of the most common clinical complaints in adult men. Several drugs used for LUTS/BPO may strongly affect sexual function and bother. The aim of this systematic review and meta-analysis was to evaluate the impact of combination therapy with alpha-blockers (AB), 5-alpha reductase inhibitors (5-ARI) on the risk of erectile dysfunction(ED) and libido alterations (LA) from randomized clinical trial (RCT). Based on the inclusion and exclusion criteria, five RCTs involving 6131 patients were included in the analysis. According to the analysis, the overall prevalence of ED and LA were significantly greater in the combination treatment group than in the AB group (7.93% versus 4.66%; OR 1.81; p < 0.0001 and 3.69% versus 2.36%; OR 1.58; p = 0.003, respectively). The combination therapy increased the risk of ED compared to monotherapy with 5-ARI (7.93% versus 6.47%; OR 1.25; p = 0.04) but not the risk of LA (3.51% versus 3.37; OR 1.03; p = 0.84). In our systematic meta-analysis, we demonstrated that combination therapy with ABs and 5-ARIs was associated with significantly higher risk of ED and LA compared with single monotherapy. Combination therapy showed similar risk of LA compared with 5-ARI monotherapy.